MATURACIONAL STAGES OF FUTSAL BEGINNERS ATHLETES FROM THE POTIGUAR SEMI-ARID REGION. (Fiep Bulletin - online, 2012)
To lead groups of genetically different natures, it is necessary for physical education teachers have knowledge about growth, development and maturation, which are essential to the formation of young athlete. The aim of this study was to analyse the maturational stages of Futsal beginner athletes from potiguar semiarid region. It was used the selfavaluation protocol in the determination of the sexual maturation by Tanner scales. The data indicate a predominance of pubescent athletes in the sample, with a much higher percentage compared to other maturational stages. We conclude that, in most cases, athletes evaluated presented similar characteristics in the stage of maturity, characterized by little variability and predominantly in general approximate results to other studies on the age group studied.
Keywords: Futsal; Maturation; Growth